2010
DOI: 10.1186/1471-2350-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inheritance and mitochondrial DNA variants in familial Parkinson's disease

Abstract: BackgroundMitochondrial function is impaired in Parkinson's disease (PD) and may contribute to the pathogenesis of PD, but the causes of mitochondrial impairment in PD are unknown. Mitochondrial dysfunction is recapitulated in cell lines expressing mitochondrial DNA (mtDNA) from PD patients, implicating mtDNA variants or mutations, though the role of mtDNA variants or mutations in PD risk remains unclear. We investigated the potential contribution of mtDNA variants or mutations to the risk of PD.MethodsWe exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Haplogroups were defined based on previously grouped mitochondrial SNPs in European populations 21 (see table 1). …”
mentioning
confidence: 99%
“…Haplogroups were defined based on previously grouped mitochondrial SNPs in European populations 21 (see table 1). …”
mentioning
confidence: 99%
“…For example, an A4336G transition in the mtDNA tRNA (Gln) gene has been found to be over-represented in PD subjects in some but not other studies (78,118,122,139). More recently, one large study found that a common nt10398G change is underrepresented in PD subjects, but a second study did not (123,151). A G5460A transition was found in one study to associate with PD, but this was not seen in other cohorts (62,122,139).…”
Section: Are Specific Mtdna Signatures Typical Of Pd?mentioning
confidence: 92%
“…2). Most initial attempts to demonstrate a genetic basis for the PD complex I defect were sequence based and either negative or, if positive, not supported through replication (62,118,122,123,139). The first durable data to strongly make a case for mitochondrial DNA (mtDNA) as an important idiopathic PD mediator come not from sequence based studies, but rather from studies of cytoplasmic hybrids, or ''cybrids'' (130).…”
mentioning
confidence: 99%
“…Overall, despite some negative studies (Latsoudis et al 2008), mtDNA haplogroups have been associated with a number of different neurodegenerative diseases, but to date, the only disease consistently associated with a different mtDNA haplogroup frequency is PD (Mancuso et al 2008a). However, recent data failed to demonstrate a bias towards maternal inheritance in familial PD (Simon et al 2010).…”
Section: Introductionmentioning
confidence: 89%